Modification of Antheraea Pernyi Silk with Reactive Quaternary Ammonium Salt of Chitosan (Journal of Fiber Bioengineering and Informatics, 2010)
Reactive quaternary ammonium salt of chitosan (RQC) with quaternary ammonium salt and reactive carbon double bonds were synthesized in two steps in order to improve the solubility and reactive properties of chitosan. Quaternized chitosan was first obtained by heterogeneous reaction of chitosan and 2, 3-epoxypropyltrimethyl ammonium chloride using isopropyl alcohol as dispersing solvent. Then RQC was prepared using the quaternized chitosan and N-(hydroxymethyl)-acrylamide. FTIR was used to characterize the structure of the synthesized RQC, and the results show that H of -NH_2 in chitosan molecules was substituted with -CH_2CH(OH)CH_2N^+(CH_3)_3 and H of OH in RQC molecule was substituted with -CH_2NHCOCH=CH_2. Antheraea pernyi (A. pernyi) silk was then modified with RQC by padding and curing method. The results revealed that the dyeing depth of treated A. pernyi silk dyed with reactive dyes increased greatly in comparison with the untreated and chitosan treated ones, and the bacterial reduction against S. aureus and E. coli of the treated A. pernyi silk fabric was more than 98% even after 20 launderings.